Formulation and Evaluation Hydrogel of Agarwood Leaf (Aquilaria malacensis Lamk.) Extract Ethanol with Combination Carbopol 940 and HPMC K4M - Noval, Noval; Harliantika, Yenny (Journal of Pharmaceutical Care Anwar Medika (J-PhAM), 2021)
Hydrogel is a topical preparation by applying it to the skin. Agarwood leaf extract is proven to contain flavonoid compounds which play a role in helping the wound healing process. The combination of carbopol and HPMC intend to cover the deficiency of carbopol when used at high concentrations and to provide an acidic ph. Know the influence combination of carbopol base 940 and HPMC K4M and the results of the evaluation of the optimal stability of the hydrogel extract of agarwood leaves. The method used is experimental with true-experimental design. The sample used is agarwood leaves in Tanah Bumbu Regency. Determination, preparation, extraction, hydrogel production and evaluation. Data were analyzed with ANOVA and Kruskal-Wallis statistics. Hydrogel formulation with a combination of carbopol base 940 and HPMC K4M gives an influence on the hydrogel formulation of agarwood leaf extract by evaluating the stability of organoleptic evaluation, homogeneity, pH, viscosity, spreadability and adhesion. The result of the formulation that can maintain the stability of evaluation during storage for 28 days at room temperature is F2. Statistical test results of pH, viscosity, spreadability and adhesion <0.05, p-value <0.05 showed a significant difference in each formula. The influence of a combination of carbopol base 940 and HPMC K4M to the hydrogel formulation of agarwood leaf extract and a good formulation is found in F2.